Organizing-for-Innovation Corporate Governance in a Digital Age - Fenwick, Mark.; Vermeulen, Erik P.M.; Kono, Toshiyuki; Joubert, Tronel (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book argues that large corporations need to implement governance practices and processes that make them better innovators and that the challenge is to identify organizational principles and practices that provide the best chance of delivering innovative products to create a meaningful consumer experience. In this context, it is important to recognize that when we address organizational forms, we are not thinking of corporate governance in the sense of managing agency costs and ensuring regulatory compliance, but the more pressing business task of putting in place organizational systems and processes that facilitate value creation through continued and sustained innovation. The book examines how the contemporary concept and discourse of corporate governance may be obsolete or, at least, is increasingly disconnected from the needs and realities of the most innovative firms today. The concept of organizing for innovation-identifying process and practices that deliver the best opportunities for innovation-needs to take centre stage. This book aims to contribute to the nascent debate in this area by bringing together a series of chapters that examine various issues related to organizing for innovation.
Organizing-for-innovation -- The board of directors as a missed opportunity -- Mobilizing institutional investors -- Corporate venturing strategies to foster innovation -- Corporate governance and new technology -- Blockchain and the disruption of the corporation -- The future of the corporation -- Regulation tomorrow. .
Keywords: Business; Management science; Information technology -- Law and legislation; Mass media -- Law and legislation; Private international law; Conflict of laws; International law; Comparative law; Business and Management; IT Law, Media Law, Intellectual Property; Private International Law, International and Foreign Law, Comparative Law; Business and Management